The Influence of Giving Biscuits of Yellow Pumpkin Seed and Capsule of Moringa Leaves on the Level of C-Reactive Protein on Pregnant Women - Musaidah, Musaidah (International Information and Engineering Technology Association, 2022)
Pregnant women are likely to have the option of receiving supplementary nourishment in the form of pumpkin seed biscuits and Moringa leaves. The purpose of this study is to see how Pumpkin Seed Biscuits and Moringa Leaf Capsules affect C-Reactive Protein (C-RP) levels in pregnant women at the Stunting Locus, Bone Regency. A Quasi-Experimental method, also known as a field trial. The Non-Randomized Pre-Test - Post Test Group Design was adopted for the research design. Participants in this study were separated into two groups: group I was given pumpkin seed biscuits and a blood-added tablet, and group II was given Moringa leaf extract capsule supplements and a blood-added tablet, with a total of 30 persons in each group. The intervention lasted 90 days and included both a pre-test and a post-test. The levels of C-Reactive Protein in group I (Pumpkin Seed Biscuits) decreased by -0.11±0.04 g/mL. The decrease in C-Reactive Protein levels in group II (Moringa Leaf Extract) was -0.09±0.04 g/mL. Moringa capsules (p=0.001) and pumpkin seed biscuits (p=0.001) had an impact on reducing C-RP levels in pregnant women. Supplemental feeding of pumpkin seed biscuits and Moringa leaf extract capsules can enhance and improve the health condition of pregnant women by lowering C-Reactive Protein levels. © 2022 WITPress. All rights reserved.